Estrategia didáctica basada en la resolución de problemas para la enseñanza y aprendizaje de los intervalos de confianza en estudiantes de ciencias económicas - Camargo Forero, Marleny (Universidad Antonio Nariño, 2023)
One of the most relevant skills for data analysis in inferential statistics is related to the interpretation and application of confidence intervals, since they are useful for estimating unknown parameters. This research addresses the problems observed in economics students of the Antonio Nariño University (UAN) regarding the erroneous understanding of the concept and lack of interpretation of this statistical object.